KEMAMPUAN RENANG ANAK IKAN PATIN (Pangasius sutchi) DI DALAM TANGKI BERARUS - Nofrizal, Nofrizal (Fakultas Perikanan dan Kelautan Universitas Riau, 2015)
Sixty seven specimens of the young catfish Pangasius sutchi were divided into three groups. The group (A) was young catfish with size (Body Length, BL±STDEV) 5.6±0.4 cm, n = 24, group (B) was 9.4±0.5 cm, n = 24, and group (C) was 15.0±0.9 cm, n = 19. All specimens were forced to swim in swimming channel of the flume tank for examined their swimming performance. The result show that the swimming speed has negative correlation on the swimming endurance. Higher swimming speed will be at lower swimming endurance for three groups of the young catfish. The bigger young catfish had higher swimming performance than smaller. Based on estimation of the burst swimming speed was 86.8 cm sec-1 for group C, 74.4 cm sec-1 for group B, and 57.5 cm sec-1 for group A. The estimation of the maximum sustained swimming speed was higher for bigger than smaller fish, as 10.9 cm sec-1 for group A, 19.7 cm sec-1 for group B and 16.4 cm sec-1 for group C. The relationship between swimming speed and swimming endurance of the young catfish are discussed in detail in this paper.